Decision Making System for Determining the Best Students at Bina Satria Medan SMKS Using the Simple Additive Weighting (SAW) Method - Wati, Suerna; Wahyuni, Dewi; Rambe, Aripin (PT. Technology Laboratories Indonesia (TechnoLabs), 2024)
Web-based Best Student Decision Making System is an application developed to assist in the decision-making process in selecting the best students. With the Web-based best student decision-making system, the decision-making process becomes more efficient, transparent, and objective. This system can integrate student data from various sources, such as academic records, attendance data, test results, and other information. In addition, this system can also apply predetermined decision-making methods, such as the Simple Additive Weighting (SAW) method. By using this system, decision makers can easily access and analyse student data comprehensively. They can also see the results of ranking the best students based on relevant criteria. This allows decision-makers to make more objective and informed decisions in the selection of the best students. The design of this application is made using PHP version 8 programming language and MySQL as the database. With this application, it can make it easier to make decisions on determining the best students.